Does coffee consumption alter plasma lipoprotein(a) concentrations? A systematic review. Issue 10 (3rd July 2018) - Penson, Peter; Serban, Maria-Corina; Ursoniu, Sorin; Banach, Maciej; ,
ABSTRACT: Coffee consumption alters plasma lipid and cholesterol concentrations, however, its effects on lipoprotein(a) (Lp(a)) have received little study. The aim of this PRISMA compliant systematic review was to examine the role of coffee on serum Lp(a). This study was prospectively registered (PROSPERO 2015:CRD42015032335). PubMed, Scopus, Web of Science and Cochrane Central were searched from inception until 9th January 2016 to detect trials and epidemiological studies investigating the impact of coffee on serum Lp(a) concentrations in humans. We identified six relevant publications describing nine experimental trials of various designs. There were a total of 640 participants across all studies and experimental groups. In short-term controlled studies, consumption of coffee, or coffee diterpenes was associated with either a reduction in serum Lp(a) of ≤11 mg/dL (6 trials, 275 participants), or no effect (2 trials, 56 participants). Conversely, one cross-sectional study with 309 participants showed serum Lp(a) was elevated in chronic consumers of boiled coffee who had a median Lp(a) of 13.0 mg/dL (range 0–130) compared with consumers of filtered coffee who had median Lp(a) 7.9 mg/dL (range 0–144). The effect of coffee on Lp(a) is complex and may follow a biphasic time-course. The type of coffee and the method of preparation appear to be important to determining the effect on Lp(a).